Business intelligence and open data: The possibilities for the derivation of valuable information in tourism domain - Blagojević, Marija; Papić, Miloš; Garabinović, Dušan (Hotel and Tourism Management, 2020)
This paper aims to introduce the concept of data analysis which could easily be implemented by anybody involved in the subject matter with basic IT knowledge and skills. The paper is divided into two parts, the first of which presents an overview of related research from two points of view: (1) publications which refer to the analysis, or the overall use of open data from the tourism domain and (2) publications which use business intelligence tools to analyse tourism data. Results indicate that there is a significant number of publications but none of them combines the two issues in the field of tourism (open data and business intelligence). The second part refers to the possibilities of using Power BI, the business intelligence tool for analysing available open data about tourism in Serbia.